Naodesheng decoction regulating vascular function via G-protein-coupled receptors: network analysis and experimental investigations - Chen, Shuhan; Niu, Ziran; Shen, Yanjia; Lu, Wendan; Zhao, Jiaying; Yang, Huilin; Guo, Minmin; Zhang, Li; Zheng, Ruifang; Du, Guanhua; Li, Li (Frontiers in Pharmacology, 2024)
Ischemic stroke (IS) is a detrimental neurological disease with limited treatment options. Recanalization of blocked blood vessels and restoring blood supply to ischemic brain tissue is crucial for the post-stroke rehabilitation. The decoction Naodesheng (NDS) composed of five Chinese botanical drugs, including Panax notoginseng (Burk.) F. H. Chen, Ligusticum chuanxiong hort, Carthamus tinctorius L., Pueraria lobata (Willd.) Ohwi and Crataegus pinnatifida Bge., is a bloodactivating and stasis-removing herbal medicine commonly used for the clinical treatment of cerebrovascular diseases in China. However, the material basis of NDS on the effects of blood circulation improvement and vascular tone regulation remains unclear. In this study, Naodesheng Effective Component Group (NECG) was found to induce relaxation of rat basilar artery rings precontracted by Endothelin-1 (ET-1) and KCl in vitro in a dose-dependent manner. By using network analysis and vasomotor experiment of cerebral basilar artery, the potential material basis underlying the vascular regulatory effects of NDS was explored furtherly. A database comprising 777 chemical metabolites of NDS was constructed. Then the interactions between various herbal metabolites of NDS and five vascular tone modulation G protein-coupled receptors (GPCRs), including 5-HT1AR, 5-HT1BR, β2-AR, AT1R, and ETBR were assessed by molecular docking. Several metabolites of NDS including Carthamus tinctorius, Crataegus pinnatifida and Panax notoginseng were found to be the main plant resources of metabolites with high docking scores. And several metabolites in NDS, including Formononetin-7-glucoside, Hydroxybenzoyl-coumaricanhydride, Methoxymecambridine, Puerarol, Pyrethrin II were found to target multiple vascular GPCRs. Furthermore, metabolites with moderate to high binding energy were verified to have good rat basilar arteries relaxing effects, and the maximum artery relaxation effects of all three metabolites namely isorhamnetin, kaempferol and daidzein were found to exceed 90%. Moreover, metabolites of NDS were found to exert a synergistic effect by interacting with vascular GPCR targets, and these metabolites may contribute to the cerebrovascular regulatory function of NDS. The study reports that various metabolites of NDS contribute to its vascular tone regulating effects and demonstrates the multicomponent and multitarget characteristics of NDS. Among them, metabolites with moderate to high binding scores in NDS may play an important role in regulating vascular function.